Epigenetic regulatory elements: Recent advances in understanding their mode of action and use for recombinant protein production in mammalian cells. Issue 7 (23rd June 2015) - Harraghy, Niamh; Calabrese, David; Fisch, Igor; Girod, Pierre‐Alain; LeFourn, Valérie; Regamey, Alexandre; Mermod, Nicolas
Abstract Successful generation of high producing cell lines requires the generation of cell clones expressing the recombinant protein at high levels and the characterization of the clones' ability to maintain stable expression levels. The use of cis‐acting epigenetic regulatory elements that improve this otherwise long and uncertain process has revolutionized recombinant protein production. Here we review and discuss new insights into the molecular mode of action of the matrix attachment regions (MARs) and ubiquitously‐acting chromatin opening elements (UCOEs), i.e. cis‐acting elements, and how these elements are being used to improve recombinant protein production. These elements can help maintain the chromatin environment of the transgene genomic integration locus in a transcriptionally favorable state, which increases the numbers of positive clones and the transgene expression levels. Moreover, the high producing clones tend to be more stable in long‐term cultures even in the absence of selection pressure. Therefore, by increasing the probability of isolating a high producing clone, as well as by increasing transcription efficiency and stability, these elements can significantly reduce the time and cost required for producing large quantities of recombinant proteins.